Wittgenstein. The Philosopher and his Works - Pichler, Alois (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2006)
This wide-ranging collection of essays contains eighteen original articles by authors representing some of the most important recent work on Wittgenstein. It deals with questions pertaining to both the interpretation and application of Wittgenstein's thought and the editing of his works. Regarding the latter, it also addresses issues concerning scholarly electronic publishing. The collection is accompanied by a comprehensive introduction which lays out the content and arguments of each contribution. Contributors: Knut Erik Tranøy, Lars Hertzberg, Georg Henrik von Wright, Marie McGinn, Cora Diamond, James Conant, David G. Stern, Eike von Savigny, P.M.S. Hacker, Hans-Johann Glock, Allan Janik, Kristóf Nyíri, Antonia Soulez, Brian McGuinness, Anthony Kenny, Joachim Schulte, Herbert Hrachovec, Cameron McEwen.